Concept of Nation in B.P. Koirala’s Atmabrittanta - Thapa, Prem (Historical Journal, 2025)
The paper explores B.P. Koirala’s late-life reflections recorded by Ganesh Raj Sharma and published in 2070 V.S. (1998/2001), titled, Atmabrittanta. The book serves as mine of memories from a prominent Nepali political leader who led the first popular revolution against the Rana-oligarchy, providing deep insights into Nepal's social, political and historical landscape. Among the various issues discussed, this paper specifically focuses on how the text presents the evolution of the concept of the nation in a modern socio-political context. Using the modern theoretical definition of a nation, the paper delves into Richard Burghart', definition of the nation and applies it to analyse koirala's narrative. The research examines the concept of the nation as muluk under the Rana regime (1846–1951) as expressed in B.P. Koirala’s Atmabrittanta (1998/2001). While analysing the text, the concept of country as muluk gradually fades away as the narrative develops, then the country as a conceptually and emotionally shared geography emerges. Finally, the textual analysis unearths the concept of nation as a shared geography of the people, rather than being owned by an oligarch or a family.